The Impact of Exports on Economic Development in Iraq (2019-2023) - Alhafith, Ali (Indonesian Journal of Public Administration Review, 2025)
Research interested in examining the relationship between exports, both non-oil commodities and oil, and Iraq's economic development in Iraq during the period 2019-2023, and Identify the degree of impact of exports on economic development of GDP using the econometrics analysis tools. The results indicated a strong moral relationship between exports and GDP, the relationship explain large proportion of changes in GDP in real terms. The most important recommendations concerning the need for the restructuring of economic sectors in Iraq, In order to achieve economic gains of economic resources before the depletion and invest in the development of non-oil commodity sectors, especially industry and agriculture.